2020
DOI: 10.1016/j.heliyon.2020.e05752
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of heat generating γ AlO– HO nanofluid inside a square cavity with multiple obstacles of different shapes

Abstract: A numerical research on uniformly heat generating γ Al 2 O 3 -H 2 O nanofluid filled square cavity with multiple obstacles of different shapes is carried out. The cavity is assumed to be heated at bottom and cooled by vertical walls with linearly varying temperature. An adiabatic condition is assumed at the top of the cavity. Circular, square and triangular shaped obstacles are considered. The mathematical model has been solved using Galerkin finite element method. Results are presented for streamlines, isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…They reported that spherical shape nanoparticles had the minimum impact on entropy generation. Ganesh et al [29] performed a numerical experiment through FEM on the convection of heat generating γ Al 2 O 3 -H 2 O nanofluid filled in a square cavity with multiple circular-, square-, and triangular-shaped obstacles. They found a higher heat transfer rate in the cavity with triangular obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that spherical shape nanoparticles had the minimum impact on entropy generation. Ganesh et al [29] performed a numerical experiment through FEM on the convection of heat generating γ Al 2 O 3 -H 2 O nanofluid filled in a square cavity with multiple circular-, square-, and triangular-shaped obstacles. They found a higher heat transfer rate in the cavity with triangular obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have analyzed how the energy flux is greater in magnitude due to concentration gradient and density spectrum. [16] numerically investigated the enhancement in thermal flow by Alumina nanoparticles filled inside a cavity with various shapes of obstacles. Also, they have analyzed the multiple rotating cells that appear inside the cavity due to multiple obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between exact solution and numerical solution approach for such arterial blood flow problems is also provided. First, we have utilized the exact solution approach to tackle this blood flow problem of curved artery having multiple stenosis and then a numerical solution approach is also considered to uncover the advantages of numerical approach for such complex geometrical structures [20][21][22][23][24][25][26]. The exact solution section contains the results of velocity, pressure gradient and wall shear stress while the numerical approach provides the 2D slice view of flow, 3D flow profile and pressure distribution at different time in this curved artery having multiple stenosis.…”
Section: Introductionmentioning
confidence: 99%